Continuity and Change in Northern Lusitania under Augustus - Armando Redentor; Pedro C. Carvalho (Gerión, 2017)
This text focuses on the archaeological traces in the northern territories of Lusitania during the Augustan period, based on regional epigraphic documents relating to the founder of the Empire. The process of territorial integration and the establishment of a new framework for population settlement are briefly presented, and the analysis points to the perceptible nuances between the littoral and the interior in a scenario of both continuity and change.